THE HISTORICAL MEMORY AND THE HISTORY OF PEACE, AFTER THE DREAM OF THE OBJECTIVE HISTORY - CAYUELA BERRUEZO, Miguel Ángel (2023)
The historical memory is a new historiography current, who seeks above all justice and truth. The case of Perú, with what happened during the years of violence (1980-2000) it’s very necessary works that are oriented towards this type of historiography. It is also important that the historical memory reach all Peruvian society, only then can the wounds left by the Peruvian process of peace be cured. This article seeks to justify the use of historical memory in the classrooms and the society, for all Peruvians do not forget the historical process marked an entire generation of Peruvians.